Peningkatan Kapasitas Digitalisasi Manajemen Data Kesehatan Bagi Kader Posyandu Dahlia 10 - Hunaifi, Nanang; Komalasari, Yunika; Dewi, Srie Wijaya Kesuma; Sulastriningsih, R. Dewi; Mauliana, Phitsa; Firmansyah, Ricky (Dinamis: Jurnal Pengabdian Kepada Masyarakat, 2025)
Posyandu functions as a health service center that provides various promotive, preventive, curative, and rehabilitative services at the village/sub-district level. Problems in managing health data at Posyandu often occur due to the lack of knowledge of cadres regarding the use of digital systems. In general, recording health data at Posyandu is done manually using book records. Without digital data management skills, Posyandu cadres who play a role as drivers in the success of health programs at the basic level are not optimal. The method used in this community service activity is digital data management training which includes several stages designed to increase the capacity of Posyandu Dahlia 10 cadres in managing digital-based health data. Digital data management training for Posyandu Dahlia 10 cadres in Wangunharja Village can improve cadres' understanding and skills in managing health data using digital technology. This training allows cadres to record, process, and report health data more efficiently and accurately, which contributes to improving the quality of health services in the community.